Storytelling Method to Improve Language Skills For Class B Children of Little Cheerful PIAUD, Pengadang Village, Central Praya District, Central Lombok Regency 2024 - Syarifuddin, Syarifuddin; Iskandar, Muhammad Rozi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to determine the storytelling method to improve language skills in children. This research uses Classroom Action Research (PTK) which consists of two cycles, each cycle consisting of three meetings. The research design uses a spiral model according to Kemmis and Mc Taggart. The main collaborator is the class teacher as teacher.Based on the results of several studies conducted, the researcher concluded that the storytelling method is good for developing language skills, especially in children. Learning was made in two cycles, namely cycle I and cycle II, each planning was made in two meetings. The results of the research showed that at each meeting there was an increase in cycle I, developing according to expectations, 3 totaled by developing very well (BSB) 5 children up to 8 children, namely 50%. Cycle II experienced a very good increase which reached the average score of 16 students who showed developing according to expectations of 4 children and developing very well. (BSB) 8 children so the total is 12, namely 75%.